Technical Efficiency Of Ginger Commodity Farms In Wonogiri District - Azziz Rohadi, Alif; Dewi Lestari, Retna; Sepfrian, Bimoseno (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Wonogiri Regency, located in Central Java Province, is the main center of ginger production in Indonesia with total production reaching 6,851,216 kg in 2019. Ginger, which consists of three main types: elephant ginger, emprit ginger, and red ginger, has high economic value as food ingredients, beverages, spices, and herbal medicines. This study aims to analyze the technical efficiency of ginger farming in Wonogiri Regency. The method used is technical efficiency analysis with the Technical Efficiency Level (TER) indicator, which shows that ginger farming in this area is not yet technically efficient. Factors affecting efficiency include seed quality, rhizome health, and farm environmental conditions. The results indicate the need for improvements in the use of production inputs to increase the efficiency and productivity of ginger farming, which in turn can increase farmers' income and support the sustainability of the ginger industry in Wonogiri Regency.